Mixed Ligand complexes of Pyrophosphate - Venkataiah, P.; Das Manwal, Dev (Asian Journal of Chemistry, 2010)
Potentiometric equilibrium measurements have been made at 30ºC for the formation of ternary complexes of pyrophosphate and Cu(II), Ni(II) with 2,2´-bipyridyl (bipy), o-phenanthroline (phen), oxalic acid (ox), iminodiacetic acid (IMDA), nitrilotriacetic acid (NTA) in 1 : 1 : 1 ratio. The ionic strength was maintained constant by using 0.2M KNO3 as the supporting electrolyte. The comparison of Δ log K values reveals that the order of stability of ternary c0mplexes is phen ≃ bipy > ox > IMDA > NTA. The order with respect to the metal ions is Ni(II) > Cu(II).